Prinsip Kehati-Hatian Serta Akibat Hukum Dalam Penerbitan Sertifikat Hak Milik Atas Tanah Oleh Kantor Pertanahan Kabupaten Kupang - Reynaldo Allendro Lomanledo; Sukardan Aloysius; Husni Kusuma Dinata (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Land issue is a problem due to the existence of land that has great value in human life often gives birth to problems, in order to avoid the increasing number of problems that occur, the state is obliged to provide legal certainty on the right of ownership of land for the community.Research using empirical juridical research. The framework of this research set out with the conception of the land law which contains the principle of prudence in the issuance of certificates and their legal consequences in order to conclude a solution for the Kupang District Land Office in terms of issuing certificates in accordance with the provisions and principles attached. Based on the results of research and discussion, it can be seen that in terms of Administration, every community service has Terms and conditions and prohibitions. The precautionary principle applied by the Kupang regency Land Office in the legal aspects of the application of legislation must be in accordance with the conditions served as a responsibility. The legal consequences that can be caused if the precautionary principle is not applied in the issuance of certificates at the Kupang regency Land Office will result in a lack of responsibility in the process of Public Service which can be fatal in the application of laws and principles in the issuance of land certificates.